Recent Advancements in Revolutionizing Cancer Therapy with Liposomal Drug Delivery - Rane, Bhushan R.; Chaure, Puja P.; Bhutekar, Santosh K.; Gawade, Sanskruti S.; Mutkule, Dinesh S.; Udmale, Aarti V.; Jain, Ashish S. (Current Cancer Therapy Reviews, 2025)
<span class=
Keywords: Liposomal nanomedicine